Derecho a la Justicia
Shot by Guatemalan human rights advocate, Jesus Tecu Osorio, expands on the earlier Rights Alert "A Massacre Remembered". Following the struggle of the indigenous Maya Achi people of Guatemala to have the truth of the genocide there in the early 1980's revealed, it includes footage of the recent trial of a few of the perpetrators. Detailing recent efforts to document the atrocities, and to secure justice through the prosecution of the masterminds of the massacres, it also includes sequences illustrating the impunity with which some perpetrators still act.